2023
DOI: 10.18186/thermal.1245298
|View full text |Cite
|
Sign up to set email alerts
|

Review on latent thermal energy storage using phase change material

Abstract: One of the appealing technologies that contributes to raising the energy storage density is latent heat thermal energy storage. The heat of fusion is isothermally stored at a temperature representing the temperature at which a phase-change material transitions between phases. The current research provides a review of how phase transition materials are used in melting and solidification. Generally, the range of working temperature extends from -20 °C to 200 °C for solidification and melting applications. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Diverse phase change materials (PCMs) with various melting and freezing temperatures are used in these systems, including eutectic, organic, and inorganic materials [8,9]. Organic PCMs, for instance, paraffin and fatty acids, possess self-nucleating properties but lower thermal conductivity and higher cost [10].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse phase change materials (PCMs) with various melting and freezing temperatures are used in these systems, including eutectic, organic, and inorganic materials [8,9]. Organic PCMs, for instance, paraffin and fatty acids, possess self-nucleating properties but lower thermal conductivity and higher cost [10].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical mantled hot water storage tanks are most common due to their ease of manufacture and superior thermal stratification. Latent heat thermal energy storage is a promising method that enhances energy storage density [21]. The heat of fusion is stored isothermally at a temperature analogous to the phasechange temperature of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Alesbe et al [44] reported on the thermal stratification of full-scale chilled water storage tanks during discharge mode under optimal conditions. The investigation involved a fullscale experimental and numerical analysis of a stratified thermal storage tank, with optimal operation conditions determined through numerous experiments.…”
Section: Introductionmentioning
confidence: 99%